Balance between Economic Growth and Social Welfare: An Inclusive Economic Approach - Priyanto Priyanto; Lisye Magdalena Liur; Heliyani Heliyani; Syamsidar Sinaga (PT. Anagata Sembagi Education, 2025)
Economic growth has long been a key indicator in measuring a country's progress. However, an excessive focus on gross domestic product (GDP) growth without considering aspects of equity and social welfare often results in social inequality and marginalization of vulnerable groups. Therefore, an inclusive economic approach is a strategic solution to balance economic growth and the improvement of social welfare in a sustainable manner. This research aims to examine how an inclusive economic approach can be applied as a comprehensive and equitable development strategy. Through literature studies and analysis of development policies in various countries, this study highlights the importance of integration between macroeconomic policies and social programs, such as strengthening the social security system, improving access to education and health, and creating equitable employment. The results show that countries that adopt an inclusive development approach tend to have stronger social resilience, sustained economic stability and higher levels of public satisfaction. Thus, a balance between growth and welfare is not only possible, but a prerequisite for achieving sustainable development. The study recommends the need for economic policy transformation that places people at the center of development and ensures the active participation of all groups in the economic process